The Identification of A Novel HIV-1 Second-Generation Recombinant form (CRF01_AE/CRF07_BC) Among Men Who Have Sex with Men in Jiangsu, China - Yueqi, Yin; Ying, Zhou; Jing, Lu; Hongxiong, Guo; Jianshuang, Chen; Yan, Xuan; Hao, Cheng; Defu, Yuan; Haiyang, Hu; Xiaoqin, Xu; Bei, Wang; Gengfeng, Fu (Current HIV Research, 2021)
Background: CRF01_AE and CRF07_BC are the two major HIV-1 virus strains circulating in China. The proportion of dominant subtypes (CRF01_AE and CRF07_BC) among MSM in Jiangsu province was over 80%. A large number of URFs have been found in China in recent years. Objective: This study aimed to report on novel HIV-1 recombinants. Methods: We constructed Phylogenetic trees using the maximum likelihood (ML) method with 1000 bootstrap replicates in IQ-TREE 1.6.8 software and determined recombination breakpoints using SimPlot 3.5.1. Results: We identified a novel, second-generation HIV-1 recombinant (JS020202) between CRF01_ AE and CRF07_BC. The analysis of near full-length genome (NFLG) showed there were at least 8 breakpoints in the virus, which differed from any previously identified CRF and URF around the world. Conclusion: Novel diverse CRF01_AE/07_BC suggested the complexity trends of HIV-1 genetics. The emergency situation of diverse recombinant strains should be monitored continuously.
Keywords: CRF